Influence of Dufour, Soret and radiation on unsteady MHD flow through a porous media past an infinite inclined vertical plate with ohmic heating: Numerical study - B. Shankar Goud; Mekala Aparna; Kottakkaran Sooppy Nisar (Results in Engineering)
This paper investigates the radiative and diffusion-thermo portions of unsteady MHD flow of a Casson fluid through a porous medium using an infinite vertical plate that is impulsively begun to flow and one whose temperature is also changing. This model also introduces Joule heating, Soret effect and the angle of inclination of the plate is considered. The finite difference method is used to assess quantitatively the characteristics of flows by transforming the governing equations into the dimensionless partial differential equations (PDEs). The non-linear non-dimensional coupled partial differential equations of the flow model are solved numerically by taking into consideration the competent implicit Crank-Nicolson finite difference process. Important flow parameters such as the shape of temperature distributions, species concentration, and the flow velocity is graphically represented with numerical values. The table indicating shear stress, Nusselt number, and Sherwood number at the plate surface is tabulated with various parameter values too. In our findings, the fluid distribution of temperature has been noted to behave in a most variable phenomenon when subjected to the effects of the Dufour parameter. As radiation factor increases, the temperature gradient decreases. Also Soret number increases with concentration profile increases